2019
DOI: 10.3389/fonc.2019.01122
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Tyrosine Kinase Inhibitors for Von Hippel–Lindau Disease: A Retrospective Study of 32 Patients

Abstract: Background: Von Hippel-Lindau (VHL) disease is an autosomal-dominant hereditary cancer syndrome. Currently, studies on tyrosine kinase inhibitor (TKI) therapy for VHL disease are scarce. In this study, we retrospectively evaluated the efficacy and safety of four TKIs in patients with VHL disease.Methods: Patients diagnosed with VHL disease who were receiving TKIs were recruited. Patients were treated with sunitinib (n = 12), sorafenib (n = 11), axitinib (n = 6), or pazopanib (n = 3). The therapeutic response w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…Sunitinib is approved for the management of pNETs and has shown stability in 5 out of 7 cases of VHL-associated pNETs ( 150 , 151 ). Another study using multiple antiangiogenic treatments (sunitinib, sorafenib, axitinib, pazopanib) showed a partial response in 4 of the 15 VHL patients with cystic or solid pancreatic tumors ( 152 ). In a phase 2 trial, 53% of VHL pancreatic lesions responded to pazopanib (anti-VEGFR 1-3, anti-PDGFR α-β, c-KIT), but most of them were serous cystadenomas ( 153 ).…”
Section: Digestive Neuroendocrine Neoplasms In Phakomatosesmentioning
confidence: 99%
“…Sunitinib is approved for the management of pNETs and has shown stability in 5 out of 7 cases of VHL-associated pNETs ( 150 , 151 ). Another study using multiple antiangiogenic treatments (sunitinib, sorafenib, axitinib, pazopanib) showed a partial response in 4 of the 15 VHL patients with cystic or solid pancreatic tumors ( 152 ). In a phase 2 trial, 53% of VHL pancreatic lesions responded to pazopanib (anti-VEGFR 1-3, anti-PDGFR α-β, c-KIT), but most of them were serous cystadenomas ( 153 ).…”
Section: Digestive Neuroendocrine Neoplasms In Phakomatosesmentioning
confidence: 99%
“… 2 Ma et al reported the effect of TKIs on metastatic RCC in 32 patients with VHL, recording partial response and stable disease rates of 28% and 47%, respectively, and median overall survival of 70 months. 5 …”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine kinase inhibitors, including sunitinib, sorafenib, axitinib, and pazopanib, have been evaluated for unresectable and/or progressive VHL-related neoplasms. 64 Among those, sunitinib was evaluated in a prospective randomized controlled trial of sporadic PNETs and prolonged progression-free survival, 65 and it may be effective for the management of PNETs in patients with VHL. [66][67][68][69] Jonasch et al 70 reported the efficacy of pazopanib in treating VHL-related neoplasms in a phase 2 study, which included 17 assessed pancreatic lesions, and there was high efficacy in reducing the size of PNETs.…”
Section: Cancer February 1 2022mentioning
confidence: 99%